APBD Implementation and Preparation Through Local Government Information System at BPKAD Bali Province (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Article 391 of the Act 23 of 2014 requires local governments to disclose to the public certain data on the maintenance of local government; this data is stored in the Information System of Regional Government. (SIPD). Budget of Regional Revenue and Expenditure (APBD) 2021 Budget Year emphasized in Permendagri No. 70 Year 2019 on the Information System of Regional Government that emphasizes on the use of SIPD, formed Sipd Plan to adapt, respond faster, dynamic, innovative and responsible start use by the local governmentAPBD is an annual operational plan to implement activities and development routine led by the government.Government leadership is counted with money coordinated with the Ministry of Home Affairs when there are problems with SIPD, unclear budgeting models in Sipd, unit prices and highest account codes in e-Components that still need to be adjusted. A lot of repairs and updates, common technical issues such as server downtime, slow network, application error, as well as general technical problems such as downtime server, slow networks, application errors, etc. and system menu is not available. This community dedication is made to BPKAD Province of Bali better understand and analyze the implementation of the drafting of the APBD SIPD 2023, identify and analyse the factors that hinder implementation, as well as better to understand and analyse efforts to counter these factors. The method used is observation, where the author will observe about the Regional Revenue and Purchasing Budget (APBD) in the Regional Government Information System (SIPD). The results of that observation show that the storage of APBD in the SIPD makes the job easier, because it is easy, effective and efficient. The conclusion is that SIPD's approach to developing APBD is good and consistent with all relevant legislation. Effective financial management of the region is methodical, efficient, and economical. This approach is also developing well, allowing APBD preparation to be easier and more transparent through SIPD applications.